Volume 9: Oil and Gas Applications; Supercritical CO2 Power Cycles; Wind Energy 2016
DOI: 10.1115/gt2016-56513
|View full text |Cite
|
Sign up to set email alerts
|

Liquid CO2 Formation, Impact, and Mitigation at the Inlet to a Supercritical CO2 Compressor

Abstract: Cycle efficiency is one of the critical parameters linked to the success of implementing a Supercritical Carbon Dioxide (sCO2) power cycle in a Concentrating Solar Power (CSP) plant application. Ambient conditions often change rapidly during operation, making it imperative that the efficiency of the plant cycle be optimized to obtain the maximum power production when sunlight is available. Past analyses have shown that operating the cycle at the critical point provides the optimum efficiency for dry operation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, it is also widely reported that the very low cycle temperature will result in a condensation area near the compressor LE. The compressor efficiency will be very poor when its inlet flow is in the two-phase region according to Poerner et al [29]. It is also found that CFD (ANSYS CFX) becomes very difficult to converge for the given temperature range above.…”
Section: A S-co 2 Recompression Brayton Cyclementioning
confidence: 98%
“…However, it is also widely reported that the very low cycle temperature will result in a condensation area near the compressor LE. The compressor efficiency will be very poor when its inlet flow is in the two-phase region according to Poerner et al [29]. It is also found that CFD (ANSYS CFX) becomes very difficult to converge for the given temperature range above.…”
Section: A S-co 2 Recompression Brayton Cyclementioning
confidence: 98%
“…A series of holes are placed at the blade inlet of the compressor impeller and used to eject a dry gas to break the liquid film formed on the airfoil. The result is the restored aerodynamic performance of the compressor and an improved lifetime of the component [58].…”
Section: Turbomachinerymentioning
confidence: 99%
“…To overcome this limitation Poerner et al in [58] proposed to adopt the gas ejection technology, widely diffused in the oil and gas wet compressors. A series of holes are placed at the blade inlet of the compressor impeller and used to eject a dry gas to break the liquid film formed on the airfoil.…”
Section: Turbomachinerymentioning
confidence: 99%
“…In a supercritical state, CO 2 has large specific heat capacity, large compressibility, large density, low viscosity and other qualities that can significantly reduce the compression work and then improve the cycle efficiency [3]. The closer the inlet condition is to the critical point, the greater the system performance is [4][5][6]. However, when the compressor inlet condition approaches the critical point, the thermophysical properties of CO 2 will change dramatically, deviate significantly from the ideal gas and show a strong real-gas effect [7,8].…”
Section: Introductionmentioning
confidence: 99%